High serum uric acid levels are a protective factor against unfavourable neurological functional outcome in patients with ischaemic stroke. Issue 5 (May 2018) - Wang, Yu-Fang; Li, Jiao-Xing; Sun, Xun-Sha; Lai, Rong; Sheng, Wen-Li
Objective: We aimed to evaluate the association between serum uric acid levels at the onset and prognostic outcome in patients with acute ischaemic stroke. Methods: We retrospectively analysed the outcomes of 1166 patients with ischaemic stroke who were hospitalized in our centre during August 2008 to November 2012. Correlations of serum uric acid levels and prognostic outcomes were analysed. Results: Men had higher serum uric acid levels and better neurological functional outcomes compared with women. There was a strong negative correlation between serum uric acid levels and unfavourable neurological functional outcomes. Generalized estimated equation analysis showed that a higher serum uric acid level (>237 µmol/L) was a protective factor for neurological functional outcome in male, but not female, patients. Among five trial of ORG 10172 in acute stroke treatment classification subtypes, only patients with the large-artery atherosclerosis subtype had a significant protective effect of serum uric acid levels on neurological outcome. Conclusions: Our study shows that high serum uric acid levels are a significant protective factor in men and in the large-artery atherosclerosis subtype in patients with ischaemic stroke. This is helpful for determining the prognostic value of serum uric acid levels for neurological outcome of acute ischaemic stroke.